Does negative-self-schema link the relationship between childhood trauma and psychotic symptoms in a community sample of Indonesians? - Octavia, Shierlen; Asih, Sali Rahadi; Jaya, Edo Sebastian (Konselor, 2019)
Childhood trauma is a risk factor that influences the development of psychotic symptoms. Negative-self-schema is a psychological response to trauma, which is known to have impact on psychotic symptoms’ level, thus postulated as the underlying mechanism linking childhood trauma and psychotic symptoms together. This research used descriptive and correlational type of research. This study examined whether negative-self-schema mediates childhood trauma and psychotic symptoms, while controlling depressive symptoms as covariates. The study recruited 397 participants from community sample of Indonesians (25.4% male; Mage = 22.28, SD = 4.93) and was conducted through online survey. Through mediation analyses, results showed that negative-self-schema significantly mediated the relationship between childhood trauma and both positive (ab = 0.08; SE = 0.04; 95% CI [0.01, 0.17]), and negative (ab = 0.08; SE = 0.03; 95% CI [0.03, 0.14]) symptoms of psychosis. This explains the importance of considering schemas’ role in translating the effect of childhood trauma to psychotic symptoms.